(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2024)
This study presents a Mixed-Integer Linear Programming (MILP) approach to optimize production planning for a poultry farm, using a medium-sized chicken meat production farm in a town in Anambra State, Nigeria as a case study. The developed model aims to maximize profit while meeting customer demand, minimizing waste, and ensuring safe stock levels. The MILP formulation considers multiple constraints, including production capacity, inventory storage, feed availability, labor hours, transportation costs, and marketing expenses. The results provide optimal production quantities, inventory levels, and resource allocation strategies. The model is solved using a commercial solver, yielding a maximum profit of ₦3,973,000.00 (2,384.19). Sensitivity analysis examines the impact of demand fluctuations, production capacity, and transportation costs on the optimal solution. The results highlight the potential of MILP to improve operational efficiency and profitability in poultry business operations, making it a valuable tool for farmers, managers, and decision-makers in the poultry industry. Therefore, this study has demonstrated the effectiveness of MILP in agricultural supply chain optimization, providing valuable insights for poultry farm managers and contributing to the development of more efficient and sustainable food production systems.